Ruptured Hepatocellular Carcinoma: Current Status of Research - Xia, Feng; Ndhlovu, Elijah; Zhang, Mingyu; Chen, Xiaoping; Zhang, Bixiang; Zhu, Peng (Frontiers in Oncology, 2022)
Background: Ruptured hepatocellular carcinoma (rHCC) is considered a rare and life-threatening manifestation; when it happens, it often requires acute and positive intervention. At present, the mechanism of rHCC development is gradually being understood while there are many kinds of rHCC treatment. From our clinical observation, the prognosis of rHCC patients is not as poor as it is currently believed. It may not be appropriate to include all patients with rHCC in T4. Main Body: The incidence of ruptured hepatocellular carcinoma is now rising. Especially in the Asian region, it can even reach 10% – 15%. The most common symptom of HCC rupture is abdominal pain, and there are now a variety of treatments for hepatocellular carcinoma rupture. With aggressive treatment, rHCC patients can also achieve a better prognosis. The patient's condition varies on admission, so the treatment methods will also be different. It is critical to identify prognostic factors simultaneously, and rHCC can be effectively managed by focusing on important prognostic factors. Conclusion: A review was carried out to analyze diagnosis, mechanism, treatment, and prognostic risk factors on this disease condition during the current situation; it is hoped that it will provide better guidance for clinicians. Moreover, patients with rHCC were managed hierarchically to prolong their prognosis.